Effects of row spacings and varieties on grain yield and economics of maize - Koirala, Saurabha; Dhakal, Akash; Niraula, Dhiraj; Bartaula, Sampurna; Panthi, Urbashi; Mahato, Mohan (Journal of Agriculture and Natural Resources, 2020)
Maize is the second most important crop of Nepal. The yield of the crop is low due to lack of appropriate plant density for the varieties. The field experiment was carried out to study the effect of different row spacings on different maize varieties at Deupur, Lamahi municipality of the dang district in province No. 5, Nepal during the rainy season from June to September, 2018. Four levels of spacings (boardcasting and three row spacings of 45, 60 and 75 cm) and two maize varieties (Rampur Composite and Arun-2) were evaluated using randomized complete block design with three replications. The highest grain yield was found in Rampur Composite and Arun-2 while they were planted with row spacing of 60 cm with plant to plant spacing of 25 cm. The highest grain yield, cob length, cob circumference, number of rows per cob, thousand grain weight were reported when maize was planted in the row spacing 60×25cm. Among the maize varieties, Rampur Composite produced the highest grain yield, cob length, cob circumference, number of rows per cob as compared to Arun-2. This study suggested that maize production can be maximized by cultivating maize varieties with row spacing of 60 cm with plant to plant spacing of 25 cm.